2017
DOI: 10.1098/rsos.170660
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of feedback update interval on the efficacy of restorative brain–computer interfaces

Abstract: Restorative brain–computer interfaces (BCIs) have been proposed to enhance stroke rehabilitation. Restorative BCIs are able to close the sensorimotor loop by rewarding motor imagery (MI) with sensory feedback. Despite the promising results from early studies, reaching clinically significant outcomes in a timely fashion is yet to be achieved. This lack of efficacy may be due to suboptimal feedback provision. To the best of our knowledge, the optimal feedback update interval (FUI) during MI remains unexplored. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In the current study only one out of 4 participants achieved ARAT improvement beyond MCID limit of 5.7, while in [22] and [46] it was 2 out of 5 and 6 out of 10 respectively. However, the percentage of average improvement in ARAT was comparable to the existing studies [22], [25], [46] and also very close to the MCID limit.…”
Section: B Comparison Of the Motor Recovery Measuressupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study only one out of 4 participants achieved ARAT improvement beyond MCID limit of 5.7, while in [22] and [46] it was 2 out of 5 and 6 out of 10 respectively. However, the percentage of average improvement in ARAT was comparable to the existing studies [22], [25], [46] and also very close to the MCID limit.…”
Section: B Comparison Of the Motor Recovery Measuressupporting
confidence: 85%
“…The average improvement in the ARAT score was 5.66 from the average baseline measurement of 17.25, which is a 32.81% improvement. A study conducted by Darvishi et al [25] achieved 36% improvement in ARAT, whereas Bundy et al [46] reported an average improvement in ARAT of 46.27% (i.e. increase of 6.2 over a baseline 13.4).…”
Section: B Comparison Of the Motor Recovery Measuresmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, in BCIs for communication, accuracy is a critical measure [43] , whereas, in therapeutic BCIs, both real-time mymargin accuracy and brain facilitation are equally important. For instance, a recent study has demonstrated the significant effect of the FUI value on the efficacy of restorative BCIs for stroke rehabilitation [44] . Overall, our results suggest that FUI customization may benefit both good and poor performers with therapeutic BCIs as well as BCIs for communication.…”
Section: Discussionmentioning
confidence: 99%
“…The classifier outputs were used to update the flexion angle of the orthoses at every FUI. For further details on the BCI setup refer to [42] , and [44] .…”
Section: Methodsmentioning
confidence: 99%